Al-Maskoot by the Imam Al-Sarkhasi (peace be upon him) (Islamic Sciences Journal, 2023)
The importance of  the subject lies  into the matters  dealt with in the current study . The subject of the current study ((al-Maskoot ) by the Imam ( al-Sarkhasi )  includes  two  things  ,i.e.  its core meaning  is concerned with  the  accurate rules  which is (al-Maskoot)  for having the fundamentalists   and jurisprudents  kept silent  and not  giving  any definition about it despite their  intensive  indications .Imam ( Sarkhasi)  is a fundamentalist  and he has not given a definition about this term , but he has refereed to its  concept and  its content  in his volumes (al-Maskoot)  and     ( The concept of  Statement)  and other conceptshe has referred to .  applications  of  this concept in various issues. The term (  al-Maskoot)   has not been given a definition  just like other  terms  and it has been recently known  as a matter  having not opposed by  the legislation  and its judgment  is indicated  with  the rule of originality.
Keywords: alsarukhsiu .. almasakut eanh .. mafhum alashar.. mustalih almaskut